Thermal, mechanical and barrier properties of rice husk ash biosilica toughened epoxy biocomposite coating for structural application - Alshahrani, Hassan; Arun Prakash, V.R. (Progress in organic coatings, 2022)
The mechanical, thermal, and barrier characteristics of an epoxy biocomposite coating made using rice husk biomass biosilica were investigated in this study. The primary objective of this research was to find out whether and how adding biosilica from biomass rice husks improve the polymeric coating material's properties and adopted as sustainable coating element. The thermo-chemical approach and an aqueous solution method were adopted to transform the rice husk ash into the biosilica and in silane treated form. The ultrasonicator was used to mix the biosilica particles with resin to create the composite coating material. The prepared coating material was then characterized using ASTM standards in order to evaluate the effects of biosilica addition. According to the results, the tensile and flexural properties were improved by the inclusion of silica particles up to 1 and 2 vol%. However the properties are reduced when the biosilica amount was increased up to 4 vol%. In contrast, the hardness and thermal conductivity of the 4 vol% of biosilica dispersed composite was 94 shore-D and 0.42 W/mK, respectively. In terms of mass loss stability, the 4 vol% biosilica dispersed composite outperformed. After the biosilica particle was added, the barrier behavior showed good resistance to oxygen penetration. However, the stability of water permeation was moderately affected. As a coating material for corrosion-prone metallic surfaces and other household coating applications, these mechanically enhanced, thermally strengthened, and barrier property strengthened biosilica-epoxy composites could be applied. •Silane treated rice husk ash biosilica epoxy coatings were successfully prepared.•Mechanical properties of coatings are improved with RHA Biosilica content.•Thermal stability of coatings are improved with RHA Biosilica content.•Highest hardness achieved was 94 Shore-D, which is highly preferred in coating.•Barrier properties were improved as biosilica content improved.